Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
This Selected Issues paper analyzes the surprising strength of remittances in Bangladesh and other countries in South Asia and the Philippines in 2009. The empirical analysis suggests that the continued strong growth of remittances in these countries is related to the resilience of non-oil GDP growth in the GCC countries and the surge in the GCC countries' hiring of migrant workers from South Asia during 2006-08. The remittances-to-GDP ratio in South Asia and the Philippines are likely to remain robust in the near term.